Therapeutic Communication in Nursing Practice: A Systematic Review of Synthesizing Evidence for Enhanched Practice and Patient Outcome - Bestfy Anitasari; Zulfikar Muhammad; Elly Dwi Masita; Tunggul Sri Agus Setyaning; Hesti Wahyuni; Agus Sudaryanto; Harisma; Risnawati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Therapeutic communication represents a fundamental component of professional nursing practice, directly influencing patient satisfaction, treatment adherence, and overall healthcare outcomes. Despite its recognized importance, nurses often encounter challenges in implementing therapeutic communication effectively due to various interpersonal, organizational, and technological complexities. Therefore, this study aims to systematically synthesize existing evidence on the dimensions, barriers, and innovative strategies of therapeutic communication in nursing practice to enhance patient outcomes. This study employed a systematic review design, analyzing articles retrieved from databases including PubMed, Scopus, and ProQuest. The search was limited to publications between 2018 and 2022. A total of 103 articles were initially identified, and after removing duplicates and conducting eligibility screening based on predefined inclusion criteria, 8 studies were selected following the PRISMA guidelines. Data were extracted and analyzed to identify key themes and patterns related to therapeutic communication. The findings revealed several critical dimensions of therapeutic communication, including empathy, emotional support, verbal and non-verbal communication skills, and the establishment of collaborative nurse–patient relationships. Additionally, common barriers such as workload, time constraints, and communication gaps were identified. The integration of digital technologies and artificial intelligence also emerged as an innovative approach to enhancing communication effectiveness in healthcare settings. In conclusion, therapeutic communication remains a vital determinant of patient-centered care and positive health outcomes. Strengthening nurses’ communication competencies, addressing systemic barriers, and leveraging technological innovations are essential strategies to optimize nurse–patient interactions. Future research should focus on developing standardized communication frameworks and evaluating the effectiveness of technology-assisted communication interventions in diverse clinical contexts.